Silício e cobre na produção de alface em cultivo sem solo - Neves, Myriam Galvão (2016)
This work aimed to evaluate the effect of silicon and copper concentrations in the nutrient solution for lettuce soilless production. Four experiments were conducted at Plant Science Department of the Federal University of Santa Maria in a closed soilless system using 3 dm3 pots with sand. Two experiments were with silicon, from June 17 to August 11 in winter and from 26 September to 24 October, 2014, in spring. Treatments were five silicon concentrations in the nutrient solution, two lettuce cultivars, Veneranda (crisphead) and Stella (butterhead), and foliar spaying of silicon seven days before harvest. Silicon concentrations in the nutrient solution were 0.0; 0.7; 1.4; 2.1 and 2.8 mmol L-1 and 0.0; 1.4; 2.8; 4.2 and 5.6 mmol L-1, respectively, and 9 mg L-1 in foliar spaying. The experimental design was a randomized factorial 5x2x2 split plot with 11 replications. Other two experiments were conducted with copper, from 27 October to 26 November, 2014, in spring and from May 8 to June 22, 2015, in fall, using the same cultivars. Copper concentrations in the nutrient solution were 0.06; 0.18; 0.3; 0.42 and 0.54 mg L-1 and 0.05; 0.75; 1.25; 1.75 and 2.25 U mg L-1, respectively. The experimental design was a randomized factorial 5x2 split plot with 11 replications. Increasing the silicon concentration reduced growth and development of plants of both cultivars and reduced also the post-harvest fresh weight loss on Stella plants. It was concluded that in the range of concentrations used in present experiments any beneficial effect of silicon on lettuce production can be expected, but it may reduce post-harvest fresh weight loss. Growth and production were reduced by copper concentrations on both cultivars and seasons and it was concluded that concentrations higher than 0.06 mg L-1 in the root medium have to be avoided.